Starphenes and Phenes: Structures and Properties - Rüdiger, Elias C.; Müller, Matthias; Freudenberg, Jan; Bunz, Uwe H. F. (Organic Materials, 2019)
Acenes have been known for a long time but their larger congeners, starphenes and phenes, have only been recently accessible as processable and characterizable derivatives. In this personalized review, we delineate the synthetic approach developed by our group over the last four years. Nickel-mediated Yamamoto coupling of ortho-dibromoacenes generates cyclotrimers. If performed in a shotgun approach, i.e. with substituted 2,3-dibromotetracene or -pentacene in the presence of ortho-dibromobenzene or ortho-dibromoveratrole, trimeric phenes and tetramers would result. Cyclotrimers formed by a pentacenylene and two phenylenes are formally dibenzo[a,c]hexacenes. A direct way to obtain these species is to employ Stille coupling of a dimethylstannafluorene with 2,3-dibromoacenes. If tetrabromoanthracenes or tetrabromopentacenes are fed into this process, tetrabenzopentacene and tetrabenzoheptacenes are easily accessible. Optical and quantum-chemical characterizations provide insight into the electronic situation and aromaticity of these species.
Keywords: acenes; phenes; starphenes